Still Jewish : a History of Women and Intermarriage in America. - McGinity, Keren R. (NYU Press, 2009)
Over the last century, American Jews married outside their religion at increasing rates. By closely examining the intersection of intermarriage and gender across the twentieth century, Keren R. McGinity describes the lives of Jewish women who intermarried while placing their decisions in historical context. The first comprehensive history of these intermarried women, Still Jewish is a multigenerational study combining in-depth personal interviews and an astute analysis of how interfaith relationships and intermarriage were portrayed in the mass media, advice manuals, and religious community-ge.